Evaluación experimental del deterioro por corrosión-erosión de materiales usados en perfiles de turbinas eólicas de eje vertical (2021)
Wind turbines are a source of clean and renewable energy generation. However, the action of several factors, such as: particulate matter, aggressive agents and the presence of humidity, can lead to the occurrence of degradation phenomena as corrosion-erosion. Those deterioration mechanisms affect the efficiency and durability of the turbines. Therefore, it is necessary to carry out degradation test to determine the resistance of the materials commonly used for the manufacture of wind turbines. The main objective of this work is to study the performance under corrosion-erosion conditions of aluminum 6000 series with and without anodized, in order to anticipate failures. Moreover, aggressive environmental conditions corresponding to the coastal zone of Colombia, specifically in the Guajira, were taken. Therefore, an abrasive particle size of 600μm, percentage of (NaCl) in the environment of 3.5%, among others, were considered as experimental conditions. Results obtained show that the material surface no anodized has greater affectation under the conditions of corrosion-erosion with an impact angle of 30°.